Barium aspiration and alveolarisation of barium in an infant: A case report and review of management - Alan F. Isles (Frontiers Media S.A., 2014)
We describe a case of bilateral inhalation and alveolarisation of barium in an infant following a barium swallow for investigation of dusky spells associated with feeds. A bronchoscopy subsequently revealed the presence of a mid-tracheal tracheo-oesophageal cleft. We review the literature on barium aspiration, its consequences and make recommendations for management.